Modernism, Fiction and Mathematics - Engelhardt, Nina (Edinburgh University Press, 2018)
Modernism in mathematics - this unusual notion turns out to provide a new perspective on central questions in and beyond literary modernism. Contrasting 'mathematical fictions' from and about the heyday of mathematical modernism, this book relates literary engagements with mathematical modernism to the wider context of modernist critiques of Enlightenment values and postmodern reassessments of modernist patterns. The analysis of canonical works by Thomas Pynchon, Hermann Broch, and Robert Musil demonstrates how mathematics is accorded a central role as a particularly telling indicator of modernist transformations, and how imaginative illustrations contribute to establishing mathematics as part of modernist culture. In its interdisciplinary exploration of modernist interrelations between the surprisingly closely related fields of mathematics and literature, the book draws on prose works by mathematicians, research in the history and philosophy of mathematics, and literary scholarship.